Determinants of road traffic accidents in Nepal (The International Research Journal of Management Science, 2022)
Purpose - The purpose of this study is to examine the relationship of poor road condition, drunk driving and weather condition on road traffic accidents in Nepal. Another purpose is to evaluate the effect of gender on over speed, poor road condition, drunk driving, weather condition and road traffic accidents.Design/methodology/ approach – The study targeted to drivers of two-wheeled and four-wheeled vehicle as population. 100 respondents were selected through a simple random sampling technique based on the police report list during last 5 years of Kathmandu valley. Primary data was sources of information for the study. It was collected by applying a well-structured survey questionnaire. Cronbatch’s Alpha coefficients were used to examine the internal consistency of the factors and an independent sample t- test was adopted to analyze differences in road traffic accidents, poor road condition, drunk driving and weather condition in terms of gender. Mean standard deviation, variance, and correlation were adopted to analyze the data in a systematic way to derive the findings for the study. Findings - The study found that there is a relationship between poor road conditions, drunk driving, and weather conditions on road traffic accidents in Kathmandu valley. The study also found that gender has no impact on poor road conditions, weather conditions, and road traffic accidents except for drunk driving. It can be concluded that poor road conditions and weather conditions are major factors causes of road traffic accidents.Research limitation/ implications - The study evaluated only three explanatory variables i.e., poor road conditions, drunk driving, and weather conditions in the entire study so that future researchers can study other factors impacting the road traffic accident of the general public with a larger sample size with new analytical tools.Originality/value –The list of the drivers who had got at least one time accident was obtained from police report. The study based on domino theory developed by Heinrich in 1980 to have outputs.